Investigation of Inflammatory and Hemostatic Parameters in Female Patients Undergoing Total Knee Arthroplasty Surgery - (:unkn) unknown (SPRINGER/PLENUM PUBLISHERS, 2008)
Tendency to hypercoagulation is a common phenomenon in primary osteoarthritis patients (POA) undergoing total knee arthroplasty (TKA) surgery, but the clinical implications of this condition are not clear. Therefore we aimed to evaluate the inflammatory and coagulation parameters in the patient group and find a possible explanation for the tendency to hypercoagulation occurring in plasma and synovia of inflamed joints. Of the evaluated factors involved in inflammation and coagulation, galectin-3, C reactive protein (CRP), erythrocyte sedimentation rate (ESR), fibrinogen, FVIIa:C, FXII:C, and platelet count increased, whereas tissue factor (TF) activity in synovia, PT, APTT and FVII:C in plasma and synovia were decreased. In conclusion, activation of inflammation and tendency to hypercoagulation is observed in preoperative plasma and synovia of patients undergoing TKA surgery.
Keywords: osteoarthritis; inflammation; coagulation; galectin-3; tissue factor; C-REACTIVE PROTEIN; TISSUE FACTOR ACTIVITY; ACUTE PHASE RESPONSE; RHEUMATOID-ARTHRITIS; SYNOVIAL-FLUID; FACTOR-XII; BINDING-PROTEIN; IN-VIVO; ACTIVATION; COAGULATION